Pelatihan Penggunaan Metode Silaba Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas Awal Sekolah Dasar: Pengabdian - Maryono; Hendra Budiono; Kuntarto, Eko; Sastrawati, Eka; Khoirunnisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to provide training and understanding for teachers in improving the initial reading skills of early grade students using the Silaba method. The activity was carried out at SDN 55/I Sridadi, Batanghari Regency, with the target participants being class teachers and subject teachers totaling 24 people. This activity method was carried out in several stages, the preparation stage in the form of coordination and permission, participant identification, preparation of training materials, development of evaluation instruments, and preparation of logistics and facilities. The next stage was the training implementation stage in the form of delivering theoretical materials, demonstrations and direct practice, workshops on making simple media for the Silaba method, discussions and questions and answers. The final stage was the evaluation and reporting stage in the form of analysis of evaluation data for activities that had been carried out. The results of community service activities that had been carried out at SDN 55/I Sridadi, showed that training on the use of the Silaba method to improve the initial reading skills of early grade students at SDN 55/I Sridadi provided understanding and satisfaction to teachers in efforts